Mentoring Inclusive Learning in Secondary Schools to Improve Teachers' Understanding and Skills in Teaching Students with Special Needs in Solo City - Kresna Agung Yudhianto; Zakaria, Nanang; Marzuki, Marzuki (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAI Al-Khiarat Pamekasan, 2024)
This study aims to enhance the understanding and skills of secondary school teachers in teaching students with special needs in Solo City by implementing an adaptive inclusive curriculum. The research method employed is the Action Research-Based Community Service (ABC) approach, which involves designing an inclusive learning model, intensive training for teachers, and ongoing monitoring and evaluation. The study began with the development of a new curriculum tailored to meet the diverse needs of students with special needs, followed by training that included effective teaching strategies and inclusive classroom management techniques. The results of the study indicate that after the implementation of the new curriculum and training, there was a significant improvement in teachers' understanding and skills in teaching students with special needs. Monitoring and evaluation revealed that students with special needs experienced an increase in learning motivation and positive interactions with their peers. Moreover, the use of modern educational technology in the teaching and learning process also had a positive impact, making the learning experience more interactive and enjoyable. Although challenges remain, such as the need for continued support for teachers, this study contributes significantly to the development of inclusive education in Solo City and can serve as a model for other schools in Indonesia to improve educational practices for all children.